The Influence of China’s ’String of Pearl’ Towards MP3EI Achievement in The Context of ASEAN Free Market 2015 - IDK Kerta Widana, Erlinda Matondang dan (Universitas Perrtahanan Indonesia (UNHAN), 2016)
Abstract â€“ String of Pearl (SoP) is Chinaâ€™s strategy to expand its influence from China Mainland to the Middle East through strategic areas, like Malacca Strait and Indian Ocean which are parts of Indonesia. This strategy will give some influences to the â€œMaster Plan of Acceleration and Expansion of Indonesia Economic Developmentâ€ (Masterplan Percepatan, Perluasan, dan Pengembangan Ekonomi Indonesia - MP3EIâ€™s) achievement that will become foundations for Indonesian economic development. The implementation of ASEAN Economic Community (AEC) that expand Chinaâ€™s access to strategic areas will affect the building of Indonesian economic corridors, especially under MP3EI framework. This study will discuss about the influence of Chinaâ€™s SoP towards Indonesian economic development, which is driven by MP3EI in AEC era. This review shows strategies available for Indonesia to minimize the influence of SoP to MP3EIâ€™s achievement in the context of free market 2015. Indonesiaâ€™s potentials to increase its advantage in diplomacy and negotiation towards China also written in the last part of this review.Keywords: String of Pearl (SoP), AEC, MP3EIAbstrak – String of Pearl (SoP) adalah strategi China untuk memperluas pengaruhnya dari China Daratan ke Timur Tengah melalui wilayah strategis, seperti Selat Malaka dan Samudera Hindia yang merupakan bagian dari Indonesia. Strategi ini akan memberi pengaruh pada